Editorial/Preface of VSI: AESMT'21 - (:unkn) unknown (My University, 2023)
The special issue “VSI: AESMT'21” aims to provide novelties in the field of the Renewables as a part of the conference “Alternative energy sources, materials and technologies (AESMT'21)”. The conference was foreseen to be held in Ruse, Bulgaria. The AESMT'21 conference was held on-line because of the bad COVID-19 situation on 14–15 June 2021.